2011
DOI: 10.1080/03079457.2011.599061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of vancomycin-resistant enterococci and extended-spectrum β-lactamase-containingEscherichia coliisolates in wild birds from the Azores Archipelago

Abstract: To study the prevalence of vancomycin-resistant enterococci (VRE) and extended-spectrum b-lactamase (ESBL)-containing Escherichia coli isolates, and the mechanisms of resistance implicated, 220 faecal samples from wild birds were collected between 2006 and 2010 in the Azores Archipelago. Samples were spread on SlanetzÁBartley agar plates supplemented with 4 mg/l vancomycin and on Levine agar plates supplemented with 2 mg/l cefotaxime for VRE and ESBL-containing E. coli isolation, respectively. vanA-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 44 publications
2
48
1
2
Order By: Relevance
“…Different percentages of VRE with acquired and intrinsic mechanisms have been previously found in wild animals, from no detection of VRE isolates in buzzards (Radhouani et al, 2012), and low VRE rates (2%) in Iberian wolves and lynxes up to percentages similar to the ones found in our study (about 6%) in crows and other wild birds (Oravcova et al, 2013;Silva et al, 2011). These variations may be due in part to differences in the methodologies applied and especially to difficulties in survey design when wild animals are studied.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Different percentages of VRE with acquired and intrinsic mechanisms have been previously found in wild animals, from no detection of VRE isolates in buzzards (Radhouani et al, 2012), and low VRE rates (2%) in Iberian wolves and lynxes up to percentages similar to the ones found in our study (about 6%) in crows and other wild birds (Oravcova et al, 2013;Silva et al, 2011). These variations may be due in part to differences in the methodologies applied and especially to difficulties in survey design when wild animals are studied.…”
Section: Discussioncontrasting
confidence: 59%
“…in wild animals in percentages very variable (0-13.5%) Mallon et al, 2002;Oravcova et al, 2013Oravcova et al, , 2014Poeta et al, 2007;Radhouani et al, 2010Radhouani et al, , 2011Radhouani et al, , 2012Santos et al, 2013;Silva et al, 2011Silva et al, , 2012. The vanA gene has been detected in these studies in E. faecalis, E. faecium, E. hirae, and E. durans (Oravcova et al, 2014;Silva et al, 2011Silva et al, , 2012, being vanA-containing E. faecium the most frequent (Oravcova et al, 2013;Radhouani et al, 2010;Silva et al, 2011Silva et al, , 2012.…”
Section: Discussionmentioning
confidence: 94%
“…Since then several reports followed (Costa et al, 2008; Poeta et al, 2008, 2009; Bonnedahl et al, 2009, 2010; Dolejska et al, 2009; Literak et al, 2009a,b, 2010; Guenther et al, 2010a,b; Hernandez et al, 2010; Pinto et al, 2010; Radhouani et al, 2010; Simoes et al, 2010; Smet et al, 2010b; Garmyn et al, 2011; Ho et al, 2011; Silva et al, 2011; Sousa et al, 2011; Wallensten et al, 2011). …”
Section: Esbls In Wildlifementioning
confidence: 99%
“…Identical resistance genes have been observed in enterococci from animals and humans, and they seem to spread freely among isolates from different reservoirs independently of their apparent host specificity [12]. At this point, wild animals play an important role, and some studies have already reported the presence of VRE and/or HLR-A enterococci in wild small mammals, rabbits, and birds [13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%